Dari Clickstream ke Riset Stream - Yohanes Suhari (Dinamik, 2003)
This article discuss research progress and future opportunities for modeling consumer choice on the Internet using clickstream data and also to compare the nature of Internet choice (as captured by clickstream data) with supermarket choice (as captured by UPC scanner panel data). Though the application of choice models to clickstream data is relatively new, and review existing early work and provide a two-by-two categorization of the applications studied to date (delineating search versus purchase on the one hand and within-site versus across-site choices on the other). The article discusses additional opportunities afforded by clickstream information, including personalization, data mining, automation, and customer valuation and also offers directions for further research in these areas. Notwithstanding the numerous challenges associated with clickstream data research.